Evaluasi Knowledge Sharing Terhadap Kinerja Pegawai Dari Aspek Komunikasi Dan Kompetensi Di Kecamatan Giriwoyo Kabupaten Wonogiri - Slamet Ibnu Mas’ud; Aris Tri Haryanto (STIE AUB Surakarta, 2026)
The purpose of this study is to determine, test and empirically analyze the evaluation of knowledge sharing on employee performance from the aspects of communication and competence in Giriwoyo District, Wonogiri Regency. The analysis techniques used are using validity and reliability tests, linearity tests, regression analysis, path analysis, t-test, F-test, coefficient of determination test and correlation analysis with a sample of 50 respondents. The results of the study show that the t-test in the first equation can be concluded that the communication and competence variables have a positive and significant effect on knowledge sharing. The results of the t-test in the second equation can be concluded that communication, competence and knowledge sharing have a positive and significant effect on performance. The results of the F test are known to be the value of F = 110.758 significance 0.000 <0.05. So it can be concluded together that the communication, competence and knowledge sharing variables have a significant effect on performance. The calculation result of the total R2 value of 0.978 can be interpreted that the variation in employee performance in Giriwoyo District, Wonogiri Regency is explained by the variables of communication, competence and knowledge sharing by 97.8% and the remaining 2.2% is explained by other variables outside the research model such as supervision and organizational culture. The conclusion of the Direct and Indirect Effects is as follows: The direct effect of communication on performance produces a greater value than the indirect effect, so it is more effective through the direct path. The direct effect of competence on performance produces a greater value than the indirect effect, so it is more effective through the direct path. Based on the results of the analysis, it can be seen that the effect of competence on performance is the most dominant variable in improving employee performance in Giriwoyo District, Wonogiri Regency.